Dynamic zinc and potassium release from a burning hyperaccumulator pellet and their interactions with inhibitive additives. (15th February 2021) - He, Yong; Liu, Siyu; Liu, Yingzu; Wang, Zhihua; Sun, Zhiwei; Xia, Jun; Zhu, Yanqun
Highlights: Temporal release of Zn and K from a burning hyperaccumulator pellet was measured. The release characteristics of different chemical groups of Zn and K were studied. Differences in the release behavior between Zn and K were compared. Inhibition effects of four additives on Zn and K release were investigated. A Ca-Al-Zn transformation mechanism promoting Zn retention efficiency was proposed. Abstract: Hyperaccumulators, as a special plant, are capable of absorbing heavy metals from contaminated soil. Thermal utilization of hyperaccumulator biomass is therefore more challenging, due to the requirement of avoiding secondary pollution of heavy metals. To investigate dynamic alkali and heavy metal release during hyperaccumulator combustion, we used multi-point laser-induced breakdown spectroscopy (LIBS) to measure zinc (Zn) and potassium (K) release from a burning Sedum alfredii pellet. The results show that 24.2% of Zn and 61.5% of K are released during the Sedum alfredii combustion through two stages, i.e., (1) devolatilization and (2) char and ash reactions. The latter is the primary release stage, accounting for 69.8% and 77.6% of the total released Zn and K, respectively. The release characteristics of different chemical groups of Zn and K are then studied by performing LIBS on Sedum alfredii treated with solvent fractionation in three sequential steps. NH4 Ac-soluble Zn and H2 O-soluble K are found to be the primary released Zn and K groups, respectively. Furthermore, inhibition effects of two synthetic additives, silica (SiO2 ) and alumina (Al2 O3 ), and two natural mineral additives, kaolin, and mica, on Zn and K release have been investigated. All the four additives achieve an inhibition efficiency higher than 55% on K release through aluminosilicate reactions and physical absorption. However, the performance of these additives on Zn retention is not as good as for K. The highest Zn retention efficiency is 37.0% achieved by Al2 O3, which can be explained by a Ca-Al-Zn transformation mechanism converting volatile Zn to Ca3 Al4 ZnO10 .